A case study on thermo-hydraulic performance of jet plate solar air heater using response surface methodology. (June 2022) - Matheswaran, Mahalingam Murugesan; Arjunan, Thottipalayam Vellingiri; Muthusamy, Suresh; Natrayan, L.; Panchal, Hitesh; Subramaniam, Shankar; Khedkar, Nitin K.; El-Shafay, A.S.; Sonawane, Chandrakanat
Abstract: In this present work, the multi-hole jet impingement approach is used to augment the performance of the jet plate solar air heater by improving the rate of heat transfer coefficient between absorber plate and impinging air. The system's usefulness is analytically analyzed, and the influence of airflow rate, length of the collector, jet diameter, pitch distances at a stream, and span-wise directions on thermo-hydraulic efficiency is investigated by adopting Response Surface Methodology (RSM). A quadratic equation is generated by using the RSM technique, which is used to predict the thermohydraulic efficiency. The results show that the optimized results of the design parameters are at the airflow rate of 0.01386 kg/s, 1.5108 m of length, 0.0046 m of jet diameter with a stream-wise pitch distance of 0.05108 span-wise pitch distance of 0 0.03414 m. The comparison results show that the RSM model evaluated values have a deviation within a range of ±1.78% compared with the analytical values developed by the model.